2019
DOI: 10.1111/jocn.14745
|View full text |Cite
|
Sign up to set email alerts
|

Nurses’ perceptions about a web‐based learning intervention concerning supportive family conversations in home health care

Abstract: This is an open access article under the terms of the Creative Commons Attribution-NonCommercial-NoDerivs License, which permits use and distribution in any medium, provided the original work is properly cited, the use is non-commercial and no modifications or adaptations are made. AbstractAims and objectives: To describe the perceptions that municipal primary healthcare nurses and municipal registered nurses had about a web-based learning intervention concerning supportive family health conversations in munic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 40 publications
0
11
0
1
Order By: Relevance
“…Therefore, when planning training programs, a tradeoff between staff training and workload must be adequately considered and addressed. Earlier research has shown that webbased training for staff within healthcare settings can generate good results (29)(30)(31). In addition to being able to participate during work hours (31), staff can also overcome access issues in the delivery of training (30).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, when planning training programs, a tradeoff between staff training and workload must be adequately considered and addressed. Earlier research has shown that webbased training for staff within healthcare settings can generate good results (29)(30)(31). In addition to being able to participate during work hours (31), staff can also overcome access issues in the delivery of training (30).…”
Section: Introductionmentioning
confidence: 99%
“…Earlier research has shown that webbased training for staff within healthcare settings can generate good results (29)(30)(31). In addition to being able to participate during work hours (31), staff can also overcome access issues in the delivery of training (30).…”
Section: Introductionmentioning
confidence: 99%
“…The research group for the present study designed a web-based education in FSN and FSNCs for nurses. The FSNC intervention and also the content and the structure of the web-based education are described in Table 1 and furthermore described in Pusa et al (2019) .…”
Section: Methodsmentioning
confidence: 99%
“…Activities and content in the seminars consisted of introduction, discussions, and practicing FSNCs in the form of role-play. The content and the structure of the course are described further in more detail in a previously published study (Pusa et al, 2019).…”
Section: Web-based Educationmentioning
confidence: 99%
“…Numerous stressors have been identified by parents of chronically ill children such as learning about the child’s illness and how to provide care and coping with flare-ups and changes (Macedo et al, 2015). Nevertheless, research has documented the essential need for family and social support, and support of health care professionals (Pusa et al, 2019).…”
Section: Introductionmentioning
confidence: 99%